PENGEMBANGAN E-MODUL MENDESAIN MOTIF DIGITAL BUSANA BERBASIS ADOBE PHOTOSHOP UNTUK PRODUK TEACHING FACTORY SISWA KELAS XI TATA BUSANA SMKN 2 BUKITTINGGI - Lathifah, Zahra; Aryati, Yulia; Nelmira, Weni; Zamil, Ilham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning digital fashion motif design at SMK Negeri 2 Bukittinggi is constrained by the limited availability of instructional media that supports both independent learning and integration with teaching factory activities. This study aimed to develop an Adobe Photoshop-based e-module for digital fashion motif design that is valid and practical as a learning medium for vocational fashion students. This research employed a Research and Development (R&D) approach using the 4D development model, consisting of the define, design, and develop stages. The research subjects included one media expert, one material expert, one fashion teacher, 12 students in the small-group trial, and 33 students in the large-group trial. Data were collected using needs analysis, validity, and practicality questionnaires with a five-point Likert scale. The results indicated that the developed e-module was categorized as highly valid, with an average validity score of 93.21% from the media expert and 96.57% from the material expert. Furthermore, the practicality test showed that the e-module was categorized as highly practical, obtaining average scores of 94.40% from the teacher, 84.24% from the small-group trial, and 86.28% from the large-group trial. Therefore, the Adobe Photoshop-based e-module for digital fashion motif design is considered valid and practical and is feasible to be used as a learning medium to support teaching factory-based learning in vocational fashion education.